2001
DOI: 10.1001/archneur.58.10.1630
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Correlates of Action Tremor in Parkinson Disease

Abstract: Action tremor was associated with rest tremor in PD, suggesting that, at least in part, action tremor is a manifestation of the underlying basal ganglia disease. Neither tremor was associated with other motor and nonmotor manifestations of PD. This in turn suggests that tremor in PD may represent an underlying pathophysiological process different from these other manifestations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
83
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 116 publications
(91 citation statements)
references
References 19 publications
7
83
0
1
Order By: Relevance
“…In regards to PD, we found that tremor phenotype can be clustered into 3 subgroups. Although we anticipated differences regarding demographic and/or clinical differences among these subgroups, these variables proved to be consistently similar across the whole sample, as suggested by the study of Louis et al 11 . We also found that tremors that can be electrophysiologically detected with more intensity at rest (subgroup 1) may not be the prototypical tremor in PD.…”
Section: Discussionmentioning
confidence: 54%
“…In regards to PD, we found that tremor phenotype can be clustered into 3 subgroups. Although we anticipated differences regarding demographic and/or clinical differences among these subgroups, these variables proved to be consistently similar across the whole sample, as suggested by the study of Louis et al 11 . We also found that tremors that can be electrophysiologically detected with more intensity at rest (subgroup 1) may not be the prototypical tremor in PD.…”
Section: Discussionmentioning
confidence: 54%
“…Second, as shown in Table 1, there was a significant difference in action tremor scores between the two patient groups. Because resting tremor and action tremor are usually highly interrelated in clinical conditions (Louis et al., 2001; Rana et al., 2014), our results are influenced by this confounding factor. Third, since the CRB‐THA‐MC loop is also involved in other tremor‐related disorders such as essential tremor, which is with overlapping manifestations with parkinsonian resting tremor at initial stages (Cagnan et al., 2014; Nicoletti et al., 2015), the specificity of thalamus for resting tremor still needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In the second study [5] instead, only PD patients who were on their usual therapeutic regimen were studied, which means any effect of pharmacological treatment on RET was not evaluated. In this regard, unpublished investigations from our group on the presence of RET in PD patients who were evaluated both off and on treatment showed that RET was more frequent when patients were evaluated off treatment.In PD, RET usually involves the upper limbs [1,[4][5][6] and is bilateral in 50% of cases [5]. Recent clinical reports have described patients with PD with RET even in the jaw [7] and tongue [8,9].…”
mentioning
confidence: 99%
“…The first, in which the aim was to evaluate occurrence and the clinical features of action tremor [4], showed that RET was present in 32% (63/197) of patients with PD. A second study [5] specifically designed to investigate RET in PD reported that 20% (42/210) of patients have RET.…”
mentioning
confidence: 99%
See 1 more Smart Citation